Phospholipid-protein structured membrane for microencapsulation of DHA oil and evaluation of its in vitro digestibility: inspired by milk fat globule membrane - Oi, Ming Lai; Chin-Ping Tan, Ping Tan; Ling, Zhi Cheong; Chen, Ying; Ge, Hui; Lai, Oi-Ming (American Chemical Society (ACS), 2020)
The present study aims to design a milk fat globule membrane (MFGM)-inspired structured membrane (phospholipid- and protein-rich) for microencapsulation of docosahexaenoic acid (DHA) oil. DHA-enriched oil emulsions were prepared using different ratios of sunflower phospholipid (SPL), proteins [whey protein concentrate (WPC), soy protein isolate (SPI), and sodium caseinate (SC)], and maltodextrin and spray-dried to obtain DHA microcapsules. The prepared DHA oil emulsions have nanosized particles. SPLs were found to affect the secondary structure of WPC, which resulted in increased exposure of the protein hydrophobic site and emulsion stability. SPL also reduced the surface tension and viscosity of the DHA oil emulsions. In vitro digestion of the spray-dried DHA microcapsules showed that they were able to effectively resist gastric proteolysis and protect their bioactivity en route to the intestine. The DHA microcapsules have a high lipid digestibility in the small intestine with a high DHA hydrolysis efficiency (74.3%), which is higher than that of commercial DHA microcapsules.